Mortgage loan Credit Collectibility as an Early Warning System in Credit Risk Mitigation (Study at Bank Mandiri in 2026) - Denis Anisa; Listri Herlina; Astrin Kusumawardani (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2026)
This study aims to measure credit risk in Home Ownership Loan (MORTGAGE LOAN) financing at Bank Mandiri using collectibility indicators as an Early Warning System (EWS) against potential Non-Performing Loans (NPL). Using a descriptive quantitative approach, the study analyzed secondary data comprising 306 accounts in Collectibility 2A (Special Mention) as of May 13, 2026, with a total outstanding balance of Rp 142.44 billion. Results show that 53% of debtors currently in Kol 2A were previously in current status (Kol 1), indicating a new wave of credit quality deterioration undetectable by NPL ratios alone. A total of 30 accounts (9.8%) are in the critical segment with arrears exceeding Rp 10 million. These findings confirm that mid-tier collectibility movements can serve as effective early warning signals, enabling banks to adopt preventive rather than reactive risk management approaches.